Signaling Alliance Commitments: Hand‐Tying and Sunk Costs in Extended Nuclear Deterrence. Issue 4 (9th April 2014) - Fuhrmann, Matthew; Sechser, Todd S.
<x xml:space="preserve">Abstract</x> How can states signal their alliance commitments? Although scholars have developed sophisticated theoretical models of costly signaling in international relations, we know little about which specific policies leaders can implement to signal their commitments. This article addresses this question with respect to the extended deterrent effects of nuclear weapons. Can nuclear states deter attacks against their friends by simply announcing their defense commitments? Or must they deploy nuclear weapons on a protégé's territory before an alliance is seen as credible? Using a new dataset on foreign nuclear deployments from 1950 to 2000, our analysis reveals two main findings. First, formal alliances with nuclear states appear to carry significant deterrence benefits. Second, however, stationing nuclear weapons on a protégé's territory does not bolster these effects. The analysis yields new insights about the dynamics of "hand‐tying" and "sunk cost" signals in international politics.